Hydrogenosome Metabolism Is the Key Target for Antiparasitic Activity of Resveratrol against Trichomonas vaginalis - Mallo, Natalia (American Society for Microbiology, 2013)
Metronidazole (MDZ) and related 5-nitroimidazoles are the recommended drugs for treatment of trichomoniasis, a sexually transmitted disease caused by the protozoan parasite Trichomonas vaginalis. However, novel treatment options are needed, as recent reports have claimed resistance to these drugs in T. vaginalis isolates. In this study, we analyzed for the first time the in vitro effects of the natural polyphenol resveratrol (RESV) on T. vaginalis. At concentrations of between 25 and 100 μM, RESV inhibited the in vitro growth of T. vaginalis trophozoites; doses of 25 μM exerted a cytostatic effect, and higher doses exerted a cytotoxic effect. At these concentrations, RESV caused inhibition of the specific activity of a 120-kDa [Fe]-hydrogenase (Tvhyd). RESV did not affect Tvhyd gene expression and upregulated pyruvate-ferredoxin oxidoreductase (a hydrogenosomal enzyme) gene expression only at a high dose (100 μM). At doses of 50 to 100 μM, RESV also caused overexpression of heat shock protein 70 (Hsp70), a protective protein found in the hydrogenosome of T. vaginalis. The results demonstrate the potential of RESV as an antiparasitic treatment for trichomoniasis and suggest that the mechanism of action involves induction of hydrogenosomal dysfunction. In view of the results, we propose hydrogenosomal metabolism as a key target in the design of novel antiparasitic drugs.